Enhancement in photo-response of CuZnS nanocrystals-based photodetector using asymmetric work function electrodes - Dahiya S.; Hazra S.; Pandey U.; Pramanik S.; Dahiya P.; Singh S.V.; Kumari N.; Pal B.N. (My University, 2025)
In this study, an efficient visible light photodetector has been fabricated by using heavy metal-free CuZnS Nanocrystals with average particle size of 13 ± 1 nm and has been synthesized by a microwave (MW) assisted synthesis technique. The optical band gap of this nanocrytstal is ∼1.7 eV and has an absorbance spectra ranging from 300 to700 nm. This low bandgap nanocrystals has been used to fabricate a photoconductor device with a CuZnS/ZnO bilayer structure. Besides, the device performance has been enhanced by using an asymmetric work-function lateral electrodes. The work-function difference between the electrodes gives a driven voltage between the electrodes, which allows faster collection of charge carriers from the device. As a consequence, a significant photocurrent is generated by the device even without any external bias. The self-biased (at 0 V) external quantum efficiency (EQE) of this device is ∼ 4 % (at 430 nm) whereas this value reaches ∼ 20 % under 2 V external bias. The device possesses the responsivity (Rλ) and detectivity (D) of 8.8 A/W and 3.8 × 1012 Jones at 320 nm respectively under 2 V external bias. © 2024 Elsevier B.V.